Newborn clinical condition assessment using infrared thermography: correlation with the Apgar score in a prospective cohort study - Letouzey, Mathilde; Diop, Samuel; Kengoum, Claude Elvire Pédié; Rousseau, Anne; Hot, Noémie; François, Juliette; Quibel, Thibaud; Berveiller, Paul; Boileau, Pascal; Jouen, François; Trabelsi, Imen; Bergounioux, Jean (Frontiers in Pediatrics, 2025)
ObjectivesThe Apgar score remains subjective in key components despite its clinical importance. An objective method using infrared thermography could enhance neonatal assessment precision. To describe early surface thermal adaptation patterns during the first 10 min after birth using infrared thermography (IRT) and to benchmark these descriptive patterns against concurrently assigned Apgar scores. This feasibility study evaluates operational characteristics of IRT as a non-contact, objective adjunct to routine assessment; it does not establish prediction or clinical utility.Study designProspective cohort of 223 full-term cesarean-delivered newborns at a tertiary maternity hospital (2021–2023). Whole-body IRT was captured at 1, 3, 5, and 10 min after birth (T1–T10). Infants were described by Apgar at 1 min (≤7 vs. ≥8).ResultsDescriptive visualizations showed observable differences in early surface temperature distributions for infants with lower Apgar scores at 1 min, with progressive warming and convergence between groups over time. Early rectal (central) temperatures in the low-Apgar group were sparsely recorded due to clinical priorities and are presented for transparency only.ConclusionsIRT can visualize thermal adaptation during immediate neonatal transition and may serve as a non-contact, objective adjunct to clinical assessment. Further outcome-based validation in larger, more heterogeneous cohorts is needed before clinical implementation.Clinical Trial Registration:ClinicalTrials.gov, identifier NCT04483869.